“‘The Tragedy of the Punch Drunk': Reading Concussion in Australian Sporting Newspapers, 1843–1954” - Townsend, Stephen (Frontiers in Sports and Active Living, 2021)
Australian cultural attitudes toward sports related concussion (SRC) are understudied. Australia has a long history of valorising combat, collision, and contact sports, in which SRC is a common occurrence. It is therefore vital to understand how sociocultural and historical factors shape Australian attitudes toward SRC, in order to more critically evaluate the decisions made by athletes, parents, coaches, and others with regards to risk and brain injury in sport. This paper analysed historical representations of SRC in Australian sporting newspapers between 1803 and 1954. Using distant reading, this analysis revealed 4 distinct periods of increased press discourse about 'concussion,' which were subject to interrogation via close reading. Close reading revealed that concussion was being reported in the Australian sporting press as early as 1859. Further analysis revealed critical and scientifically informed discussions about the delayed effects of concussion in 1901, systemic critiques of sporting organisations' response to concussion in 1906, and evidence of a limited concussion crisis in Australian boxing during the early 1930s. The findings of this research show that concussion was not only being reported in Australian newspapers throughout the late 19th and early 20th centuries but it was subject to critical and informed commentary that has striking similarities with current debates about SRC. Despite this, widespread systematic changes to Australian sport did not occur until recently. This raises important questions about the political and institutional factors that prevented a major concussion crisis from developing in Australia during the early 20th century, and prompts us to further consider the distinguishing features that facilitated the development of the current crisis.